2000
DOI: 10.1007/s000590050003
|View full text |Cite
|
Sign up to set email alerts
|

The "Final Common Pathway" Hypothesis and Inherited Cardiovascular Disease

Abstract: The genetic basis of a number of inherited cardiovascular diseases has been elucidated over the last few years, including the long QT syndromes, hypertrophic cardiomyopathy and dilated cardiomyopathy. While genetic heterogeneity has been demonstrated in most of these diseases, a pattern has emerged, specifically that genes encoding proteins with similar functions or involved in the same pathway are responsible for a particular disease or syndrome. Based on this observation we proposed the "final common pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
1
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(89 citation statements)
references
References 83 publications
4
79
1
4
Order By: Relevance
“…Specifically, ␣-E-catenin is highly expressed in the adherens junction of the cardiac intercalated disc, and perturbations in its expression are associated with dilated cardiomyopathy, a disease associated with and shown to influence the cytoskeleton. 1,2,20,23,24 Because ␣-E-catenin is dynamically linked to the cytoskeleton in other cell types, we hypothesized that ␣-E-catenin would play an essential role in cardiac adherens junction ultrastructure and function in the myocardium in vivo. ␣-Catenin is required for early vertebrate embryonic development 8 and is ubiquitously expressed; thus, we utilized a conditional approach to explore its functional role in the myocardium.…”
Section: Clinical Perspective P 1055mentioning
confidence: 99%
“…Specifically, ␣-E-catenin is highly expressed in the adherens junction of the cardiac intercalated disc, and perturbations in its expression are associated with dilated cardiomyopathy, a disease associated with and shown to influence the cytoskeleton. 1,2,20,23,24 Because ␣-E-catenin is dynamically linked to the cytoskeleton in other cell types, we hypothesized that ␣-E-catenin would play an essential role in cardiac adherens junction ultrastructure and function in the myocardium in vivo. ␣-Catenin is required for early vertebrate embryonic development 8 and is ubiquitously expressed; thus, we utilized a conditional approach to explore its functional role in the myocardium.…”
Section: Clinical Perspective P 1055mentioning
confidence: 99%
“…However, the genes responsible for DCM are less well characterized than those for HCM. The mutation or deletion of some myofibrillar and extracellular matrix proteins, such as α-CA, β-MHC, cTnI, cTnT, TM, alpha-actinin, desmin, titin and dystrophin, were observed (Table 3) (215)(216)(217). Some studies in knock-out mice and humans have offered insight into the putative role of these proteins in maintaining sarcomere integrity (176,211).…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…The mutant proteins most likely act in a dominant negative way and lead to the appearance of desminpositive aberrant intrasarcoplasmic and electron-dense granular filamentous aggregates, and these aggregates are characteristic of human desmin-related myopathy. The pathomechanism for this entity is not yet fully understood, but the defective desmin protein was seen to result in an impaired force transmission or in contraction-induced cellular damage (215). A genetic analysis of patients suffering from dominantly inherited or desmin-related myopathy revealed that the mutant desmin interferes with the normal assembly of intermediate filaments, resulting in fragility of the myofibrils and severe cardiac dysfunction (236).…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…The 'final common pathway' hypothesis by Towbin and Bowles was one of the first attempts to link structural protein mutations to the major presentations of heart failure: most notably dilated and hypertrophic cardiomyopathies (Bowles et al, 2000). According to this hypothesis, DCM arises primarily from alterations in cytoskeletal proteins, whereas ARVC/D is caused by structural weakening of the desmosome, which predisposes the RV to fibrosis and dilation (Stokes, 2007).…”
Section: Current Insights Into Mechanisms Of Arrhythmogenesis In Animmentioning
confidence: 99%